Membaca dialog Yesus dan Nikodemus melalui lensa persahabatan - Butarbutar, Adolf Bastian (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2024)
This study examines the dialogue between Jesus and Nicodemus in John 3:1-21 through the theological lens of friendship, offering a fresh perspective on this pivotal Gospel narrative. Using narrative hermeneutics in conjunction with biblical theological analysis, this research demonstrates that friendship functions not merely as an anthropological category but as a fundamental theological concept for understanding mission, soteriology, and ecclesiology. The analysis reveals that Jesus' approach to Nicodemus embodies characteristics of authentic friendship: recognition, intellectual engagement, mutual respect, and transformative commitment. Drawing on contemporary friendship theology, particularly Jürgen Moltmann's